ความรู้แห่งผู้ปกครองที่แท้ของเซโนฟอน : การศึกษาเชิงปรัชญาการเมือง - ประเสริฐ พัฒนผลไพบูลย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
The purpose of this study is to understand Corpus Xenophonteum, the core or the essential concept of Xenophon, that exists on his whole texts, by using the method of interpretation of political philosophy which emphasize on the perennial question as well as the eternity of order or nature(phusis) that related to the Good and justice, which Xenophon quests for. The hermeneutic clues of Xenophon’s texts show that a gentleman(kalonkagathon), who understand the nature of human being, the association of human being as city-state(polis), the order of the good(noble, justice, and good), the good constitution(politeia), and the good ruler, is the way of good life by linking between philosophical life and political life together. In other words, a gentleman, who think, speak, and does in a good and noble manner, is the one or a group of suitable people who understand the art of politics, the true political science, that makes human being become noble and good as much as possible in this living world. The art of politics is the most important art(techne) or science(episteme) because this knowledge possesses "the better" or strength(kreittonos) that can provide a good suitable law and order to the public as well as to makes the whole become noble and good by political virtue that lead to harmony(homonoia) and justice. Therefore, this knowledge that makes human being become good and noble, by examining themselves or Know Thyself (gnothi sauton), is the only beneficial and useful thing for learning and quests for, because only through this knowledge can makes human suitable to rule themselves well, rule their households(and friends) well, and rule their country well.